The Role of Immersive Technology and Platform Trust in Shaping Consumer Purchase Intention: A Systematic Literature Review in Digital Shopping Environments - Yulianti, Erna (Dinasti Publisher, 2025)
The rapid advancement of digital experience technologies and the widespread adoption of online shopping platforms have fundamentally transformed how consumers evaluate, perceive, and make purchasing decisions. Consequently, research on digital consumer behavior has become increasingly critical. This study aims to identify and synthesize key factors influencing online consumer behavior by examining the roles of immersive digital technologies, social influences, individual psychological factors, and mediating variables such as trust, perceived risk, and platform quality. This study employs a Systematic Literature Review (SLR) based on the PRISMA framework, analyzing 37 peer-reviewed articles published between 2015 and 2025 from various countries. The findings reveal that immersive technologies such as Augmented Reality (AR), visual dynamism, interactivity, and recommender systems significantly shape consumers’ cognitive and emotional responses, thereby enhancing purchase intention and impulsive buying behavior. Social factors including social media marketing, electronic word-of-mouth (e-WOM), influencer credibility, and social presence strengthen perceived value and consumer trust. Furthermore, psychological factors such as hedonic motivation, attitude, personal norms, emotional intelligence, and self-control play a crucial role in moderating consumer responses to digital stimuli. Overall, online consumer behavior is a multidimensional phenomenon shaped by the simultaneous interaction of technological, social, psychological, and trust-related factors. This study contributes a comprehensive conceptual synthesis that advances theoretical understanding and offers practical implications for digital platform developers, marketers, and policymakers